1984
DOI: 10.1152/jappl.1984.56.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Strength and cycle time of high-altitude ventilatory patterns in unacclimatized humans

Abstract: Respiration was monitored with magnetometers in 12 healthy supine young adults at sea level and in an altitude chamber at simulated high altitudes of 8,000, 9,000, 11,000, and 14,000 ft. Periodic breathing that was strong enough to include apnea at the time of minimum ventilation was seen in all subjects at high altitude. Cycle time of periodic breathing ranged from 12 to 34 s. On average across the population the incidence of periodic breathing increased with altitude. Cycle time of the periodic pattern incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…is lower than those reported previously in a hypoxic chamber (WAGGENER et al, 1984) and at altitudes higher than 5,300 m (LAHIRI et al, 1983;SUTTON et al, 1979;WEST et al, 1986) but is similar to that in the studies of WELL et al(1978) and HACKETT et al (1987). Figure 2 shows the relationship between ventilatory chemosensitivities and PB index.…”
Section: Disordered Breathing At Altitudesupporting
confidence: 86%
See 2 more Smart Citations
“…is lower than those reported previously in a hypoxic chamber (WAGGENER et al, 1984) and at altitudes higher than 5,300 m (LAHIRI et al, 1983;SUTTON et al, 1979;WEST et al, 1986) but is similar to that in the studies of WELL et al(1978) and HACKETT et al (1987). Figure 2 shows the relationship between ventilatory chemosensitivities and PB index.…”
Section: Disordered Breathing At Altitudesupporting
confidence: 86%
“…In this case, circulation time should have been prolonged. On the other hand, WAGGENER et al (1984) and VoGEL and HARRIS (1967) found increased cardiac output in the hypoxic chamber or at high altitude. In these cases, circulation time should have been shortened.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Transient reductions in breathing amplitude to v50% baseline over 5-10 s were also scored as apnoeas/hypopnoeas if they occurred as part of a periodic breathing pattern with waxing and waning of ventilation with periods of hyperventilation alternating with central apnoeas/ hypopnoeas over at least three successive cycles ( fig. 1) [24,25]. Central apnoeas/hypopnoeas were identified by absence of rib cage-abdominal asynchrony [14].…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…Increased during respiratory muscle fatigue or dysfunction Apnea and hypopnea detection Diagnostic components of sleep apnea/hypopnea syndrome and periodic breathing. Hypopnea defined as !50% baseline Vt for O10 s. Apnea defined as !25% baseline Vt for O10 s Apnea and hypopnea classification Phase relation between chest and abdomen classifies apnea/hypopnea events into central, mixed, and obstructive (1808) types Magnitude of periodic Vt oscillations Magnitude of oscillations of periodic breathing and Cheyne-Stokes respiration cycles associated with apnea or hypopnea (Waggener et al, 1984) Cycle time of periodic Vt oscillations Cycle length of periodic breathing and Cheyne-Stokes respiration. Longer cycle time points to a basis in chronic heart failure, shorter times to idiopathic central sleep apnea syndrome (Waggener et al, 1984) Forced expiratory volume in 1 s (FEV 1.0 ) Requires a voluntary breathing maneuver.…”
Section: Vivologic Physiologic Data Analysis and Displaymentioning
confidence: 99%